Development Increase Investment Of The Private Sector In Uzbekistan (The Peerian Journal, 2022)
The article looks in the conditions of the modern crisis, having a balanced economy becomes a condition of effective regulation of social-economic processes in the region. One of the factors of economic development becomes activation of market mechanisms of private sector self-regulation. Flexibility and high adaptiveness of the private sector are important advantages and predispositions of having a balanced economy. This manuscript attempts to consider different points of view on the process of achieving balance in the economy of the region, determining the role of the private sector in this process.